Political Economy of Development and Underdevelopment. Re-Visiting Dependence Theory - Hidalgo-Capitán, Antonio Luis (Iberoamerican Journal of Development Studies, 2019)
In this article we have tried to answer to the question ‘why some economies are developed and other economies are underdeveloped?’ For this, we have enacted an explanation which is inspired on the ideas of Dependence Theory authors and which is based on three premises: both phenomena have common causes; both phenomena have opposite and symmetric causes; and both phenomena are the result of historic process which arrive to ours days. Then we have identified like underdevelopment causes: the colonial exploitation; the trade exploitation; the financial exploitation; the plenty curse; the heritage dual social structure; the no-permanent presence of Social Rule of Law; and the global apartheid. And the development causes will be: the colonial exploitation; the trade exploitation; the financial exploitation; the scant resources distribution; the plural social structure; the permanent presence of Social Rule of Law; and the global apartheid. CITE AS: Hidalgo-Capitán, A. L. (2012). Economía Política del Desarrollo y el Subdesarrollo. Revisitando la Teoría de la Dependencia. Iberoamerican Journal of Development Studies, 1 (1): 4-27